Digital Habitus and the Reconfiguration of Religious Authority: Evidence from Muhammadiyah Youth in Indonesia - Hatib Rachmawan; Muhammad Ridha; Muhammad Fasih Hulisan; Zhu Weihang (UM Purwokerto Press, 2026)
This study examines the reconfiguration of religious authority in the digital era by analyzing the role of digital habitus among Muhammadiyah youth in Indonesia. Using a quantitative survey design involving 78 respondents, the study explores how digital religious literacy shapes the construction of religious authority within digital environments. The findings indicate that respondents demonstrate a high level of digital engagement, with 82.1% actively accessing religious content online, 79.5% able to evaluate the credibility of religious information, and 80.7% consistently verifying content before sharing it. Furthermore, 69.3% of respondents actively participate in the dissemination of religious content, highlighting their role in the circulation of religious knowledge. Despite this high level of epistemic capacity, respondents exhibit only moderate discursive confidence, revealing a gap between knowledge and perceived authority. Moreover, the strong concentration of preferences toward a limited number of religious figures suggests that religious authority remains structured rather than fully decentralized. Drawing upon the theory of mediatization and Bourdieu's concept of habitus, this study argues that religious authority in the digital era undergoes a process of hybridization, combining the distributed accessibility of digital networks with the reproduction of new hierarchical structures based on visibility and symbolic legitimacy. These findings challenge the assumption that digitalization automatically leads to the democratization of religious authority, demonstrating instead that authority has become increasingly complex, negotiated, and multilayered. Accordingly, this study proposes a hybrid model of religious authority that integrates structural transformation, individual practices, and network-based knowledge circulation in contemporary Muslim societies.